The duality of women scholars of color transforming and being transformed in the academy - Jean-Marie, Gaëtane; Grant, Cosette M.; Irby, Beverly (Research on women and education., 2014)
The seven chapters address long-standing concerns from first-hand perspectives regarding women of color faculty in the academy, the marginalization of women of color scholars in the academy and the benefits of mentoring support. Discussion of such are threaded throughout this book. Mentoring has been a practice of leadership since Greek times, and research has documented the advantages of mentoring. Aligned with the authors espoused mentoring perspectives in this book, is the coined concept of "synergistic mentoring" Accordingly, "Synergistic mentoring is defined as a mentor and mentee working together collaboratively to (a) generate a greater good for both, (b) integrate diverse perspectives into the context, and (c) construct together an otherwise unattainable goal attempted independently.The authors of this book seek to enlighten, dynamic and critical discussions by and about women of color in the academy. Conceivably the most intriguing part of each chapter is the methodological approaches used to address race, gender, and social justice in the academy. Qualitative methods dominate the chapters with effective use of personal narratives and the lived experiences of the participants. The voices of those often ignored or forgotten are examined building on the legacy of women of color in the academy who paved the way for this generation and future scholars of color. Moreover, the chapters presented herein challenge assumptions, perspectives and beliefs about the significance of women of color scholars in the academy. They are provocative and provide direction for future research that advance knowledge and understanding for a better society based on social justice, equity and equal opportunity. They also give voice to both the shared diverse and common experiences of this group of women scholars of color and provide useful guidance and new perspectives on transforming the world's academics into more inclusive and equitable environments around the globe (Thomas & Hollenshead, 2001). Ultimately, outcomes from these collections of scholarly discourse, may have important implications for effective policy and program practice that raise important questions about institutional commitments that advocate for the advancement of women of color in the academy.